PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI INTRINSIK PADA KARYAWAN OUTSOURCING PT CAHAYA BINTANG PLASTINDO GRESIK - Anugrahini Irawati; Irma Puji Cahyani; Helmi Buyung Aulia Safrizal (Eco-Entrepreneur, 2018)
This study entitled Influence Workload on Employee Performance through Intrinsic Motivation on Outsourcing Employees PT Cahaya Bintang Plastindo Gresik. This study aims to: (1) To determine the effect of workload on employee performance of PT Cahaya Bintang Plastindo Gresik, (2) To know the effect of workload on intrinsic motivation of PT Cahaya Bintang Plastindo Gresik employees, (3) To know the effect of intrinsic motivation on employee performance PT Cahaya Bintang Plastindo Gresik, and (4) To know the effect of work load on employee performance through intrinsic motivation as intervening variable at PT Cahaya Bintang Plastindo Gresik. This study uses quantitative methods whose population is all employees outsourcing PT. Cahaya Bintang Plastindo Gresik which amounts to 121 employees. The sample used is 93 employees with Proportionate Stratified Random Sampling sampling technique. Hypothesis in this research are: (1) Work load has positive and significant effect to employee's performance, (2) Work load has positive and significant effect to employee intrinsic motivation, (3) Intrinsic motivation have positive and significant effect to employee performance, (4) work has a positive and significant effect on employee performance with intrinsic motivation as intervening variable. Based on path analysis result show that: (1) Work load positively and significantly influence to the performance employee value 6,463 (2) Work load positively and significantly influence to intrinsic motivation with influence value 0,796, (3) The intrinsic motivation have positive and significant influence to the performance employee with influence value 0,300, (4) Work load have positive and significant effect to employee performance through intrinsic motivation as intervening variable with influence value 0,238.